2023
DOI: 10.1371/journal.pone.0281934
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing analysis in families with recurrent pregnancy loss: A pilot study

Abstract: One to two percent of couples suffer recurrent pregnancy loss and over 50% of the cases are unexplained. Whole genome sequencing (WGS) analysis has the potential to identify previously unrecognized causes of pregnancy loss, but few studies have been performed, and none have included DNA from families including parents, losses, and live births. We conducted a pilot WGS study in three families with unexplained recurrent pregnancy loss, including parents, healthy live births, and losses, which included an embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…A recent study utilizing whole-genome sequencing (WGS) in couples experiencing recurrent miscarriages revealed that SV, associated with embryo loss and fetal death, affects the functionality of well-known reproductive genes, including FBN2 [34]. Genetic variations in FBN2 can also contribute to pregnancy loss [35].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study utilizing whole-genome sequencing (WGS) in couples experiencing recurrent miscarriages revealed that SV, associated with embryo loss and fetal death, affects the functionality of well-known reproductive genes, including FBN2 [34]. Genetic variations in FBN2 can also contribute to pregnancy loss [35].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, due to the different delivery hospitals of the participants, although we have tried to collect data on obstetric deliveries as much as possible, there may be some bias. Recurrent miscarriage is above all a di cult area in reproductive medicine because its causes are often unknown and diagnostic and therapeutic strategies are based on scarce evidence [29] , [30]. Chinese Government will allow up to three children per couple will do little to boost startlingly low fertility rates [31] In addition to encouraging couples of childbearing age to increase the number of hospitals where they have children, we hope to focus on more potential risk factors that may jeopardize the fertility of women of childbearing age, and to call attention to the importance of fertility preservation for couples of childbearing age and to alleviate the stresses that they may face in the process of childbearing.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal chromosomal abnormalities are associated with 50% of first-trimester miscarriages, while the etiology of pregnancy loss in the remaining 50% of cases with normal karyotype and chromosomal microarray analysis remains unexplained (Hardy and Hardy 2018 ). Recent exome sequencing studies have begun to uncover deleterious variants in specific genes that cause euploid pregnancy loss (Najafi et al 2021 ; Rajcan-Separovic 2020 ; Robbins et al 2019 ; Workalemahu et al 2023 ; Xiang et al 2021 ; Zhao et al 2021 ). However, the spectrum of genes associated with human lethality and pregnancy loss remains understudied.…”
Section: Introductionmentioning
confidence: 99%